Formation of Share Performance Expectation: A Micro Level Process Perspective - Gniewosz, Gerhard (The International Journal of Accounting and Business Society, 1994)
This paper provides a descriptive account ofthe function of the annual report in the formation of share performance expectation at the micro level of an institutional investor. Some of the major ï¬ndings of time-series research are subjected to a closer scrutiny at the micro level within the context of real life complexities. The focus is on three major aspects: (1) the structure of financial statement analysis. (2) the function of the prior forecast error, and (3) the analystâ€™s forecasting process. The study concentrates on the process of formation ofshare performance expectation on receipt ofthe annual report, rather than at any other point in time. The study does not focus on the process of communicating the expectation (i.e. the actual recommendation), or the actual investment process itself.